A supercritical modified graphite negative electrode material and processing method thereof

Through the combined treatment of supercritical carbon dioxide technology and water-soluble aluminum salt, the problem of uneven coating of natural graphite is solved, achieving uniform coating of natural graphite and improving battery cycle life.

CN119381426BActive Publication Date: 2025-04-11XIAN MOSHICHUAN ELECTRONIC TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411391503.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-04-11
Estimated Expiration
2044-10-08

AI Technical Summary

Technical Problem

The prior art is difficult to achieve uniform and complete coating of natural graphite materials, resulting in local side reactions with the electrolyte and affecting the battery cycle life.

Method used

The natural graphite is pretreated by supercritical carbon dioxide technology, and water-soluble aluminum salt is introduced on this basis, and a stable and uniform coating layer is formed through ultrasonic dispersion and high-temperature carbonization.

Benefits of technology

The uniform coating of natural graphite is achieved, the side reaction with the electrolyte is reduced, and the cycle life of the battery is improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention belongs to the technical field of secondary battery materials. More specifically, it relates to a supercritical modified graphite negative electrode material and a processing method thereof. The method of the present invention includes: mixing natural graphite, an ethanol solution and a surfactant, ultrasonically dispersing to obtain an ultrasonic dispersion; transferring the obtained dispersion to a supercritical high-pressure reactor, then starting to inject carbon dioxide, and reacting supercritically at a constant temperature and pressure, until the reaction is completed, releasing the pressure, and discharging to obtain a supercritical dispersion; adding a water-soluble aluminum salt to the supercritical dispersion, stirring and dissolving, adjusting the pH to 4.5-5.5, keeping warm and standing, filtering, washing and drying to obtain pretreated natural graphite; mixing the pretreated natural graphite and the asphalt solution evenly, evaporating to remove the solvent, and obtaining asphalt-coated natural graphite; carbonizing the asphalt-coated natural graphite at high temperature, cooling, and discharging to obtain a supercritical modified graphite negative electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of secondary battery materials, and more specifically, relates to a supercritical modified graphite negative electrode material and a processing method thereof. Background Art

[0002] When natural graphite is used as the negative electrode material for lithium-ion batteries, coating it with asphalt is a common method in this field. The main function of coating is to improve the electrochemical properties of natural graphite as the negative electrode material of lithium-ion batteries, especially to reduce the side reactions between natural graphite and electrolyte, thereby reducing the problem of decreased cycle life due to the consumption of electrolyte.

[0003] At present, common coating methods include liquid-phase coating and solid-phase coating. In liquid-phase coating, asphalt is dissolved in an appropriate solvent to form a uniform asphalt solution, and then natural graphite is added for mixing and ultrasonic treatment to form a uniform suspension. Afterwards, asphalt-coated natural graphite is obtained by evaporating the solvent and high-temperature carbonization treatment; in solid-phase coating, asphalt is mixed with natural graphite by dry method, and then heat-treated under high temperature conditions so that asphalt forms an amorphous carbon layer on the graphite surface, thereby improving the electrochemical properties of graphite. There is a problem when processing the above two coating methods, that is, it is difficult for asphalt to fully and uniformly coat natural graphite. Moreover, even if relatively sufficient coating can be achieved, during the high-temperature carbonization process, the carbonized layer is easily caused by the internal stress formed by the high temperature, resulting in the collapse of the coating structure, which leads to defects in the final coating effect and other problems, thereby exposing part of the interface of natural graphite. Summary of the invention

[0004] The technical problem to be solved by the present invention is that, for natural graphite materials, when raw materials such as asphalt are used for coating, it is difficult to achieve uniform and complete coating of natural graphite, which leads to local side reactions with electrolyte, thereby affecting the battery cycle life. The present invention provides a supercritical modified graphite negative electrode material and a processing method thereof.

[0005] The purpose of the present invention is to provide a supercritical modified graphite negative electrode material.

[0006] Another object of the present invention is to provide a method for processing supercritical modified graphite negative electrode material.

[0007] The above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0008] A method for processing a supercritical modified graphite negative electrode material, the specific processing steps comprising:

[0009] After mixing natural graphite, ethanol solution and surfactant, ultrasonically disperse the mixture to obtain ultrasonic dispersion liquid; transferring the obtained dispersion liquid to a supercritical high-pressure reactor, then starting to inject carbon dioxide, and performing supercritical reaction under heat and pressure, and after the reaction is completed, releasing the pressure and discharging the mixture to obtain a supercritical dispersion liquid;

[0010] The heat preservation and pressure preservation are: temperature of 40-42°C and pressure of 14-16MPa;

[0011] Adding water-soluble aluminum salt to the supercritical dispersion, stirring to dissolve, adjusting the pH to 4.5-5.5, keeping warm and standing, filtering, washing and drying to obtain pretreated natural graphite;

[0012] After the pretreated natural graphite and the asphalt solution are uniformly mixed, the solvent is evaporated to remove the solvent, thereby obtaining asphalt-coated natural graphite;

[0013] The asphalt-coated natural graphite is carbonized at high temperature, cooled, and discharged to obtain a supercritical modified graphite negative electrode material.

[0014] Beneficial effects of the above scheme:

[0015] The above scheme pre-treats natural graphite by using supercritical carbon dioxide technology. During the treatment process, due to the high diffusivity and compressibility of carbon dioxide, it can diffuse and penetrate into the interlayers of natural graphite, thereby widening the interlayer spacing of natural graphite, thereby effectively reducing the interaction force between natural graphite layers; and, during the supercritical treatment process, carbon dioxide molecules can form a strong repulsive effect with the hydrophilic groups of the surfactant, thereby causing the hydrophilic groups to aggregate and form a hydrophilic core. In this process, the curvature of the surfactant changes, thereby forming the driving force required to widen the interlayer spacing of artificial graphite.

[0016] The reason for using supercritical treatment is that the process is essentially a physical change to natural graphite and does not produce substantial changes to the chemical properties of natural graphite.

[0017] On the basis of the above treatment, a water-soluble aluminum salt is further introduced into the supercritical dispersion liquid, so that the aluminum ions diffuse and penetrate rapidly between the natural graphite layers, and after the pH is adjusted, the dispersion liquid is kept warm for a long time, for example, it can be placed at a temperature of 65-70°C for 12-24 hours, so that the aluminum ions are gradually converted into aluminum hydroxide and embedded in the natural graphite layers. In this way, during the filtering and drying process, the interlayer spacing after the supercritical treatment can be effectively supported by the deposited aluminum hydroxide to prevent the interlayer spacing from shrinking back to the initial state;

[0018] In particular, the presence of aluminum hydroxide can facilitate the smooth diffusion and penetration of asphalt into the interior, thereby achieving sufficient and uniform coating of the natural graphite interface, and even during the high-temperature carbonization process, aluminum hydroxide can still be converted into aluminum oxide, and achieve effective support for the internal interface of natural graphite, avoiding internal pore collapse, and together with the products formed by asphalt carbonization, construct a stable and uniform coating layer to achieve modification of natural graphite. Therefore, due to the uniform and stable coating of the material, the existence of local side reactions between the electrolyte and the electrolyte caused by inadequate coating can be effectively reduced, which causes the problem that the battery cycle life is always difficult to guarantee.

[0019] Furthermore, the ultrasonic dispersion liquid includes the following raw materials in parts by weight:

[0020] 10-15 parts of natural graphite, 100-110 parts of ethanol solution with a mass fraction of 18-22%, and 3-5 parts of surfactant.

[0021] Furthermore, the surfactant is selected from any one of polyvinyl pyrrolidone, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, hexadecyltrimethylammonium bromide, Tween 20, Tween 40 and Tween 60.

[0022] Furthermore, the amount of the water-soluble aluminum salt is 4.5-6.5% of the mass of the natural graphite.

[0023] Furthermore, the water-soluble aluminum salt is selected from any one of aluminum chloride, aluminum nitrate and aluminum sulfate.

[0024] Furthermore, the pretreated natural graphite and the asphalt solution are mixed at a mass ratio of 1:(8.5-9.5); and the asphalt solution is obtained by mixing and dissolving asphalt and tetrahydrofuran at a mass ratio of 1:(8-10).

[0025] Furthermore, the high temperature carbonization includes: heating to 1180-1250° C. at a heating rate of 6-8° C. / min in an argon atmosphere, and carbonizing at this temperature for 4-6 hours.

[0026] A supercritical modified graphite negative electrode material is obtained by processing using the above processing method. DETAILED DESCRIPTION

[0027] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0028] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0029] Example 1

[0030] According to weight, 10 parts of natural graphite, 100 parts of 18% ethanol solution, and 3 parts of surfactant are taken in sequence;

[0031] Among them, natural graphite is selected with a D50 of 15 μm;

[0032] The surfactant is selected from polyvinyl pyrrolidone;

[0033] After mixing natural graphite, ethanol solution and surfactant, ultrasonic dispersion was performed at a temperature of 45°C and an ultrasonic frequency of 80kHz for 40 minutes to obtain an ultrasonic dispersion liquid;

[0034] The obtained ultrasonic dispersion liquid was transferred to a supercritical high-pressure reactor, and then carbon dioxide was injected. The supercritical reaction was carried out at a temperature of 40°C and a pressure of 14 MPa for 4 hours. After the reaction was completed, the pressure was released to normal pressure and the material was discharged to obtain a supercritical dispersion liquid.

[0035] Adding water-soluble aluminum salt to the supercritical dispersion, stirring and dissolving with a stirrer at a speed of 300 r / min, adjusting the pH to 4.5, keeping the temperature at 65° C. for 12 hours, filtering, washing and drying to obtain pretreated natural graphite;

[0036] The amount of the water-soluble aluminum salt is 4.5% of the mass of the natural graphite;

[0037] The water-soluble aluminum salt is selected from aluminum chloride;

[0038] After the pretreated natural graphite and the asphalt solution are mixed, the mixture is stirred at a speed of 800 r / min for 4 hours with a stirrer, and then evaporated to remove the solvent to obtain asphalt-coated natural graphite;

[0039] The pretreated natural graphite and the asphalt solution are mixed at a mass ratio of 1:8.5; and the asphalt solution is obtained by mixing and dissolving asphalt and tetrahydrofuran at a mass ratio of 1:8;

[0040] The asphalt-coated natural graphite is transferred into a carbonization furnace, heated to 1180°C at a heating rate of 6°C / min in an argon atmosphere, carbonized for 4 hours, cooled to room temperature with the furnace, and discharged to obtain a supercritical modified graphite negative electrode material.

[0041] Example 2

[0042] According to weight, 12 parts of natural graphite, 105 parts of 20% ethanol solution, and 4 parts of surfactant are taken in sequence;

[0043] Among them, natural graphite is selected with a D50 of 15 μm;

[0044] The surfactant is selected from sodium lauryl sulfate;

[0045] After mixing natural graphite, ethanol solution and surfactant, ultrasonic dispersion was performed at a temperature of 45°C and an ultrasonic frequency of 80kHz for 40 minutes to obtain an ultrasonic dispersion liquid;

[0046] The obtained ultrasonic dispersion was transferred to a supercritical high-pressure reactor, and then carbon dioxide was injected. The supercritical reaction was carried out at a temperature of 41°C and a pressure of 15 MPa for 4.6 hours. After the reaction was completed, the pressure was released to normal pressure and the material was discharged to obtain a supercritical dispersion.

[0047] Adding water-soluble aluminum salt to the supercritical dispersion, stirring and dissolving with a stirrer at a speed of 300 r / min, adjusting the pH to 4.8, keeping the temperature at 67° C. for 18 hours, filtering, washing and drying to obtain pretreated natural graphite;

[0048] The amount of the water-soluble aluminum salt is 5.5% of the mass of the natural graphite;

[0049] The water-soluble aluminum salt is selected from aluminum nitrate;

[0050] After the pretreated natural graphite and the asphalt solution are mixed, the mixture is stirred at a speed of 800 r / min for 4 hours with a stirrer, and then evaporated to remove the solvent to obtain asphalt-coated natural graphite;

[0051] The pretreated natural graphite and the asphalt solution are mixed in a mass ratio of 1:9; and the asphalt solution is obtained by mixing and dissolving asphalt and tetrahydrofuran in a mass ratio of 1:9;

[0052] The asphalt-coated natural graphite is transferred into a carbonization furnace, heated to 1200°C at a heating rate of 7°C / min in an argon atmosphere, carbonized for 5 hours, cooled to room temperature with the furnace, and discharged to obtain a supercritical modified graphite negative electrode material.

[0053] Example 3

[0054] According to weight, 15 parts of natural graphite, 110 parts of 22% ethanol solution, and 5 parts of surfactant are taken in sequence;

[0055] Among them, natural graphite is selected with a D50 of 15 μm;

[0056] The surfactant is selected from sodium dodecylbenzene sulfonate;

[0057] After mixing natural graphite, ethanol solution and surfactant, ultrasonic dispersion was performed at a temperature of 45°C and an ultrasonic frequency of 80kHz for 40 minutes to obtain an ultrasonic dispersion liquid;

[0058] The obtained ultrasonic dispersion liquid was transferred to a supercritical high-pressure reactor, and then carbon dioxide was injected. The temperature was 42°C and the pressure was 16MPa. The supercritical reaction was carried out at constant temperature and pressure for 5 hours. After the reaction was completed, the pressure was released to normal pressure and the material was discharged to obtain a supercritical dispersion liquid.

[0059] Adding water-soluble aluminum salt to the supercritical dispersion, stirring and dissolving with a stirrer at a speed of 300 r / min, adjusting the pH to 5.5, keeping the temperature at 70° C. for 24 hours, filtering, washing and drying to obtain pretreated natural graphite;

[0060] The amount of the water-soluble aluminum salt is 6.5% of the mass of the natural graphite;

[0061] The water-soluble aluminum salt is selected from aluminum sulfate;

[0062] After the pretreated natural graphite and the asphalt solution are mixed, the mixture is stirred at a speed of 800 r / min for 4 hours with a stirrer, and then evaporated to remove the solvent to obtain asphalt-coated natural graphite;

[0063] The pretreated natural graphite and the asphalt solution are mixed at a mass ratio of 1:9.5; and the asphalt solution is obtained by mixing and dissolving asphalt and tetrahydrofuran at a mass ratio of 1:10;

[0064] The asphalt-coated natural graphite is transferred into a carbonization furnace, heated to 1250°C at a heating rate of 8°C / min in an argon atmosphere, carbonized for 6 hours, cooled to room temperature with the furnace, and discharged to obtain a supercritical modified graphite negative electrode material.

[0065] Comparative Example 1

[0066] The difference between this comparative example and Example 1 is that no water-soluble aluminum salt is added, and the other conditions remain unchanged.

[0067] Comparative Example 2

[0068] Compared with Example 1, this comparative example differs in that supercritical carbon dioxide is not used for treatment. Specifically:

[0069] According to weight, 10 parts of natural graphite, 100 parts of 18% ethanol solution, and 3 parts of surfactant are taken in sequence;

[0070] Among them, natural graphite is selected with a D50 of 15 μm;

[0071] The surfactant is selected from polyvinyl pyrrolidone;

[0072] After mixing natural graphite, ethanol solution and surfactant, ultrasonic dispersion was performed at a temperature of 45°C and an ultrasonic frequency of 80kHz for 40 minutes to obtain an ultrasonic dispersion liquid;

[0073] Adding water-soluble aluminum salt to the ultrasonic dispersion, stirring and dissolving with a stirrer at a speed of 300 r / min, adjusting the pH to 4.5, keeping the temperature at 65° C. for 12 hours, filtering, washing and drying to obtain pretreated natural graphite;

[0074] The amount of the water-soluble aluminum salt is 4.5% of the mass of the natural graphite;

[0075] The water-soluble aluminum salt is selected from aluminum chloride;

[0076] After the pretreated natural graphite and the asphalt solution are mixed, the mixture is stirred at a speed of 800 r / min for 4 hours with a stirrer, and then evaporated to remove the solvent to obtain asphalt-coated natural graphite;

[0077] The pretreated natural graphite and the asphalt solution are mixed at a mass ratio of 1:8.5; and the asphalt solution is obtained by mixing and dissolving asphalt and tetrahydrofuran at a mass ratio of 1:8;

[0078] The asphalt-coated natural graphite is transferred into a carbonization furnace, heated to 1180°C at a heating rate of 6°C / min in an argon atmosphere, carbonized for 4 hours, cooled to room temperature with the furnace, and discharged to obtain a supercritical modified graphite negative electrode material.

[0079] The performance tests were performed on the products obtained in the examples and comparative examples. The specific test methods and test results are as follows:

[0080] The products obtained in the above embodiments or comparative examples were used as negative electrode active materials, respectively. The negative electrode active material, conductive carbon black Super-P and carboxymethyl cellulose were mixed in a mass ratio of 9:0.6:0.4, and deionized water was added as a solvent, and stirred evenly to prepare a negative electrode slurry; then the negative electrode slurry was scraped on the surface of the copper foil, and dried at 100°C for 12h to obtain a negative electrode sheet, which was cut into discs with a diameter of 12mm, wherein the surface density of the active material on the surface of the negative electrode sheet was controlled at 2.68mg / cm 2; In the glove box, a CR2032 battery shell was selected, lithium sheets were used as counter and reference electrodes, and a porous polypropylene membrane (Clegard 2320) is used as a diaphragm, and a button-type half-cell is assembled in the order of a negative electrode plate, a diaphragm, an electrolyte, a lithium sheet, a gasket, and a shell, wherein the electrolyte is selected as a formula of 1 mol / L lithium hexafluorophosphate dissolved in a ternary mixture of ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate in a volume ratio of 1:1:1; after the battery is assembled and sealed, it is allowed to stand at room temperature for 36 hours to perform electrochemical performance testing; a CT2001A blue electric test system is used with a test voltage range of 0.005-3.0V to perform constant current charge and discharge tests on the above-mentioned battery; specifically, charging at a rate of 0.33C until the charging voltage reaches 3.0V, constant voltage charging is performed until the current reaches 0.05C, charging is stopped, and it is regarded as fully charged, and then discharging at a rate of 0.5C to a voltage of 0.005V, which is regarded as fully discharged, and the cycle performance test is performed in this way until the battery capacity decays to less than 80% of the initial capacity. The ambient temperature for the electrochemical performance test was 25°C; the detailed test results are shown in Table 1;

[0081] Table 1: Product performance test results

[0082] Cycle performance / cycle Example 1 2155 Example 2 2162 Example 3 2171 Comparative Example 1 1680 Comparative Example 2 1656

[0083] It can be seen from the test results in Table 1 that the product obtained by the present invention has good cycle performance.

[0084] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for processing a supercritical modified graphite negative electrode material, characterized in that: The specific processing steps include: After mixing natural graphite, ethanol solution and surfactant, ultrasonically disperse the mixture to obtain ultrasonic dispersion; The obtained dispersion is transferred to a supercritical high-pressure reactor, and then carbon dioxide is injected to perform a supercritical reaction under heat and pressure. After the reaction is completed, the pressure is released and the material is discharged to obtain a supercritical dispersion; The heat preservation and pressure preservation are: temperature of 40-42°C and pressure of 14-16MPa; Adding water-soluble aluminum salt to the supercritical dispersion, stirring to dissolve, adjusting the pH to 4.5-5.5, keeping warm and standing, filtering, washing and drying to obtain pretreated natural graphite; After the pretreated natural graphite and the asphalt solution are uniformly mixed, the solvent is evaporated to remove the solvent, thereby obtaining asphalt-coated natural graphite; The asphalt-coated natural graphite is carbonized at high temperature, cooled, and discharged to obtain a supercritical modified graphite negative electrode material.

2. The method for processing a supercritical modified graphite negative electrode material according to claim 1, characterized in that: The ultrasonic dispersion comprises the following raw materials in parts by weight: 10-15 parts of natural graphite, 100-110 parts of ethanol solution with a mass fraction of 18-22%, and 3-5 parts of surfactant.

3. A method for processing a supercritical modified graphite negative electrode material according to any one of claims 1 or 2, characterized in that: The surfactant is selected from any one of polyvinyl pyrrolidone, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, hexadecyltrimethylammonium bromide, Tween 20, Tween 40 and Tween 60.

4. The method for processing a supercritical modified graphite negative electrode material according to claim 1, characterized in that: The amount of the water-soluble aluminum salt used is 4.5-6.5% of the mass of the natural graphite.

5. The method for processing a supercritical modified graphite negative electrode material according to claim 4, characterized in that: The water-soluble aluminum salt is selected from any one of aluminum chloride, aluminum nitrate and aluminum sulfate.

6. The method for processing a supercritical modified graphite negative electrode material according to claim 1, characterized in that: The pretreated natural graphite and the asphalt solution are mixed at a mass ratio of 1:(8.5-9.5); and the asphalt solution is obtained by mixing and dissolving asphalt and tetrahydrofuran at a mass ratio of 1:(8-10).

7. The method for processing a supercritical modified graphite negative electrode material according to claim 1, characterized in that: The high temperature carbonization comprises: heating to 1180-1250° C. at a heating rate of 6-8° C. / min in an argon atmosphere, and carbonizing at the temperature for 4-6 hours.

8. A supercritical modified graphite negative electrode material, characterized in that: The product is obtained by the processing method described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • Silica aerogel / micro-expanded graphite composite material and preparation method and application thereof

    CN109950493A

  • Graphite negative electrode material and preparation method thereof

    CN116425151A